The focus and timing of gaze matters: Investigating collaborative knowledge construction in a simulation-based environment by combined video and eye tracking - Lämsä, Joni; Kotkajuuri, Jimi; Lehtinen, Antti; Koskinen, Pekka; Mäntylä, Terhi; Kilpeläinen, Jasmin; Hämäläinen, Raija (Frontiers in Education, 2022)
Although eye tracking has been successfully used in science education research, exploiting its potential in collaborative knowledge construction has remained sporadic. This article presents a novel approach for studying collaborative knowledge construction in a simulation-based environment by combining both the spatial and temporal dimensions of eye-tracking data with video data. For this purpose, we have investigated two undergraduate physics student pairs solving an electrostatics problem in a simulation-based environment via Zoom. The analysis of the video data of the students’ conversations focused on the different collaborative knowledge construction levels (new idea, explication, evaluation, and non-content-related talk and silent moments), along with the temporal visualizations of the collaborative knowledge construction processes. The eye-tracking data of the students’ gaze, as analyzed by epistemic network analysis, focused on the pairs’ spatial and temporal gaze behavior. We illustrate how gaze behavior can shed light on collaborative knowledge construction in terms of the quantity of the talk (e.g., gaze behavior can shed light on the different activities of the pairs during the silent moments), quality of the talk (e.g., gaze behavior can shed light on the different approaches when constructing knowledge on physical phenomena), and temporality of collaborative knowledge construction processes (e.g., gaze behavior can shed light on (the lack of) attempts to acquire the supporting or contrasting evidence on the initial ideas on the physical phenomena). We discuss the possibilities and limitations of gaze behavior to reveal the critical moments in the collaborative knowledge construction processes, pinpointing those features of the simulation environment that attract unnecessary visual attention and lead the collaborative knowledge construction processes in an undesired direction.